Granite-waste as a sustainable lead-free X-ray shielding concrete: Effect of composition on the strength and ability to counter X-ray - Nasyrah R, Muhammad Nur; Ardiansyah, Ardiansyah; Alomari, Ali Hamed; Heryanto, Heryanto; Abdullah, Bualkar; Abdul Karim, Muhammad Khalis; Tahir, Dahlang (Elsevier, 2026)
In this study, granite-waste incorporation in laboratory-scale cementitious composites was investigated to develop lead-free shielding materials for diagnostic X-rays while evaluating the associated mechanical trade-off. Five compositions (SG00-SG80; 0-80 wt% granite) were prepared and cured for 28 days. X-ray attenuation was measured at 40, 44, and 50 keV (10 mAs) using a Siemens Multimobil 2.5 portable X-ray system, and incident/transmitted dose was recorded with a calibrated RaySafe X2 Survey Sensor. Linear attenuation coefficient (μ), mass attenuation coefficient (μ/ρ), half-value layer (HVL), tenth-value layer (TVL), and mean free path (MFP) were calculated and benchmarked against NIST XCOM data. Density increased from 1.1433 to 1.2203 g/cm3 as granite content increased. At 50 keV, μ increased from 0.228 cm−1 (SG00) to 0.519 cm−1 (SG80), while HVL decreased from 3.051 to 1.334 cm, indicating improved shielding at higher granite fractions. Compressive strength showed an optimum at SG20 (52.91 kg/cm2) and decreased at higher granite contents (5.23 kg/cm2 at SG80). Correlation analysis at 50 keV showed compressive strength was negatively correlated with μ (r = −0.927) and positively correlated with HVL/TVL/MFP (r approximately 0.89), confirming a composition-dependent strength-shielding trade-off. Experimental attenuation agreed well with XCOM at 40-44 keV, with modest deviation at 50 keV attributable to broad-beam polychromatic effects. These findings support granite waste as a promising sustainable aggregate for low-energy X-ray shielding, with SG20 suitable for balanced mechanical-shielding performance and higher granite fractions suitable for non-structural shielding applications.